2018
DOI: 10.13080/z-a.2018.105.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of Triticum aestivum and Triticum durum for technological quality properties in Serbia

Abstract: Proteins are important in determining the nutritional value of wheat, and among them gluten determines the baking quality of bread wheat and pasta-making technological properties of wheat. By assessing genetic parameters of wheat quality traits, it is possible to elucidate potential for improvement. The plant material consisted of 30 genotypes of bread and durum wheat of worldwide origin. The trials were sown at three locations in Serbia during two vegetation seasons 2010-2011 and 2011-2012. Protein content, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…This result was in agreed with finding of Taghouti et al, who reported that the protein content of the genotypes varied from 12.52 to 16.28% with an average value of 14.58% [23]. This result also was in line with the finding of Branković et al, who reported that protein content was varied from 12.4 to 15.4% in bread wheat [24]. The differences among the genotype were important.…”
Section: Mean Comparison Of the Genotypes For Grain Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…This result was in agreed with finding of Taghouti et al, who reported that the protein content of the genotypes varied from 12.52 to 16.28% with an average value of 14.58% [23]. This result also was in line with the finding of Branković et al, who reported that protein content was varied from 12.4 to 15.4% in bread wheat [24]. The differences among the genotype were important.…”
Section: Mean Comparison Of the Genotypes For Grain Qualitysupporting
confidence: 92%
“…Similarly higher and wider range in comparison to results Branković et al, who reported that the wet gluten content ranged from 22.8% to 30.3% for bread wheat genotypes [24]. The highest mean value for wet gluten was obtained for Hidasse (58.82%), while the lowest value was recorded for genotype ETBW8427 (36.49%) ( Table 5).…”
Section: Mean Comparison Of the Genotypes For Grain Qualitysupporting
confidence: 47%
“…Gluten has a major contribution in the unique baking quality of wheat by conferring water absorption capacity, cohesiveness, viscosity and elasticity on dough (WIESER, 2007). Wet gluten and dry gluten are positively associated with protein content, the first mentioned representing common flour specification required by endusers in the food industry (BRANKOVIĆ et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It shows wheat breeders how traits are affected by G, E, and G × E interaction (Kaya & Akcura, 2014). The heritability has already been studied for various quality traits in wheat except for Glutograph parameters (Branković et al, 2018; Rakszegi et al, 2016). High heritability values (86.2%–95.8%) were calculated for GPC, wet gluten content (WGC), Zeleny sedimentation value (ZSV), and Alveograph deformation energy (W) value by Branković et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The heritability has already been studied for various quality traits in wheat except for Glutograph parameters (Branković et al, 2018; Rakszegi et al, 2016). High heritability values (86.2%–95.8%) were calculated for GPC, wet gluten content (WGC), Zeleny sedimentation value (ZSV), and Alveograph deformation energy (W) value by Branković et al (2018). The heritability values for GlutoPeak, Farinograph, and Extensograph parameters, W, SDS sedimentation (SDSS), and GPC were calculated in the range of 0.60–0.83 (Michel, Gallee, Löschenberger, Buerstmayr, & Kummer, 2017).…”
Section: Introductionmentioning
confidence: 99%